IMPLEMENTATION OF SOCIAL RISK DEVELOPMENT MITIGATION THROUGH STAKEHOLDERS RELATIONS - Yuningsih, Ani; Maulani, Izni Nur Indrawati; Harum, Alexandria Cempaka (Jurnal Audience: Jurnal Ilmu Komunikasi, 2024)
The urgency for infrastructure development in various regions in Indonesia continues to increase. The increase in population makes population mobility increase. This condition encourages the growth of new business centers in various regions of Indonesia, so that they do not only focus on the islands of Java and Bali. Kalimantan is a promising business center. Kalimantan's attractiveness comes from supporting facilities such as road access, international airports, ports, electricity, railroads, economic and cultural centers, and so on. Development is an intervention effort carried out deliberately and planned with the aim of improving previous living conditions. However, the vulnerability of the development process due to different attitudes from society, intervention from NGOs and other obstacles can make development risky. To understand and assess social risk mitigation, a case study of social potential and risks was carried out. The research locations were carried out in a number of sub-districts in the East Kalimantan and South Kalimantan regions. The aim of this research is to find a model for a communication approach for local government coordination with internal stakeholders, find a model for a communication approach for collaboration between local government and external stakeholders, and state the reasons for strengthening local government relations in mitigating social risks in infrastructure development in the East and South Kalimantan regions.